Penerapan Metode Theorema Bayes dalam Mendiagnosa Penyakit Hepatitis Berbasis Web - Andreas Ariyanto Rangga; Felysitas Ema Ose Sanga; Wilhelmina Rita Malo (Universitas Medan Area, 2023)
Hepatitis is caused by various factors such as viral infections, toxic substances such as alcohol, certain drugs. Many cases of hepatitis have subtle or subclinical symptoms. In Indonesia, the part of East Nusa Tenggara, hepatitis disease is low, because most people who suffer from mild hepatitis C positive in pregnant women are mostly relatively high. More than double the national average of 2.2%. Based on the above problems, an application in the form of an expert system is needed to diagnose liver disorders, one of which is the Bayes theorem method. Bayes' theorem is a method that applies rules relating to probabilities or probability values. Hepatitis patients can die within a few weeks if not treated immediately. It will be used as an initiative to conduct studies on intelligent systems for diagnosing hepatitis. Therefore, this research creates a system that can help doctors treat hepatitis. With the concept of an expert system able to analyze problems and draw conclusions about the transfer of expert knowledge to the system. The results of the studies tested have shown the multiplication result of the highest classification value with the Bayes method and is a type of liver disorder that the patient suffers from.